2015
DOI: 10.1111/eva.12261
|View full text |Cite
|
Sign up to set email alerts
|

Life history traits and phenotypic selection among sunflower crop–wild hybrids and their wild counterpart: implications for crop allele introgression

Abstract: Hybridization produces strong evolutionary forces. In hybrid zones, selection can differentially occur on traits and selection intensities may differ among hybrid generations. Understanding these dynamics in crop–wild hybrid zones can clarify crop-like traits likely to introgress into wild populations and the particular hybrid generations through which introgression proceeds. In a field experiment with four crop–wild hybrid Helianthus annuus (sunflower) cross types, we measured growth and life history traits a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 94 publications
3
15
0
Order By: Relevance
“…Similar increased germination with crop hybridization has been reported for many crop-wild complexes, including sunflower (Snow et al 1998;Presotto et al 2014;Pace et al 2015), lettuce (Hooftman et al 2007), and rice (Dong et al 2011). In our study, the increased germination of BAR x CROP did not result in differential seedling establishment relative to BAR, however, under real situations with intraspecific and interspecific competition, early emergence may increase the competitive ability of hybrids (Snow et al 1998;Kost et al 2015;Gioria & Pyšek 2017). Similar results have been reported for crop-wild sunflower hybrids in the native area (Mercer et al 2006;Alexander et al 2014;Kost et al 2015), as hybrids produced on wild plants showed high overwinter survival (due to maternal effects on seed dormancy), and rapid germination during early spring (due to nuclear crop alleles).…”
Section: Maternal Effects On Seed Dormancy Regulate the Timing Of Emesupporting
confidence: 89%
See 1 more Smart Citation
“…Similar increased germination with crop hybridization has been reported for many crop-wild complexes, including sunflower (Snow et al 1998;Presotto et al 2014;Pace et al 2015), lettuce (Hooftman et al 2007), and rice (Dong et al 2011). In our study, the increased germination of BAR x CROP did not result in differential seedling establishment relative to BAR, however, under real situations with intraspecific and interspecific competition, early emergence may increase the competitive ability of hybrids (Snow et al 1998;Kost et al 2015;Gioria & Pyšek 2017). Similar results have been reported for crop-wild sunflower hybrids in the native area (Mercer et al 2006;Alexander et al 2014;Kost et al 2015), as hybrids produced on wild plants showed high overwinter survival (due to maternal effects on seed dormancy), and rapid germination during early spring (due to nuclear crop alleles).…”
Section: Maternal Effects On Seed Dormancy Regulate the Timing Of Emesupporting
confidence: 89%
“…Such differences in autumn emergence between biotypes were predicted from germination experiments under controlled conditions (Presotto et al 2014;Hernández et al 2017), and they confirm that, in wild sunflower, primary seed dormancy is key to preventing out-of-season germination. Similar results have been reported for sunflower in the native area (Alexander et al 2014;Kost et al 2015), as wild populations showed high overwinter survival whereas most cultivated seeds did not overwinter, mostly due to high autumn germination and subsequent winter mortality.…”
Section: Primary Seed Dormancy Is Key To Preventing Out-of-season Gersupporting
confidence: 86%
“…Research in early‐generation crop‐wild hybrids grown under wild or weedy conditions has shown fitness advantages of hybrids over wild populations (Campbell & Snow, ; Kost, Alexander, Jason Emry, & Mercer, ; Mercer, Andow, Wyse, & Shaw, ) and that some crop‐like traits are favoured over multiple generations (Campbell, Snow, & Sweeney, ). These findings support the view that crop‐derived alleles have the potential to be advantageous in wild environments, but they did not attempt to identify underlying causal alleles or elucidate their genomic context.…”
Section: Introductionmentioning
confidence: 99%
“…additionally, or alternatively, be restricted by local adaptation to particular pockets of diverse landscapes, as has also been demonstrated in maize in of southern Mexico [9]. To discern local adaptation in this system, we would need to determine the degree to which particular germination or emergence traits influence survival and fruit production in the resulting plants [e.g., 60,61]…”
Section: Plos Onementioning
confidence: 99%